2004
DOI: 10.1007/s00383-004-1334-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for the management of appendicular mass in children

Abstract: Appendicitis is the most common surgical emergency in pediatric surgery. In the presence of an appendicular mass, surgical management can be difficult. We evaluate the results of appendix mass management both with immediate operation and conservative treatment over a period of 5 years. Forty children who presented with appendicular mass over a period of 5 years were reviewed. Their mean age was 7.6+/-2.7 years, and the mean duration of symptoms was 7.8+/-2.7 days. We evaluated the children in two groups: The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
59
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 7 publications
7
59
0
1
Order By: Relevance
“…[19] In present study maximum number of patients belonged to age group 21-30, followed by second highest in 31-40 with mean age of 32.43. Similar age distribution has been reported by Cash and Frazee (2012) [12] and Kefagias et al (2008) [13].…”
Section: Discussionsupporting
confidence: 89%
“…[19] In present study maximum number of patients belonged to age group 21-30, followed by second highest in 31-40 with mean age of 32.43. Similar age distribution has been reported by Cash and Frazee (2012) [12] and Kefagias et al (2008) [13].…”
Section: Discussionsupporting
confidence: 89%
“…The complication rate of 36% amongst the patients treated with early surgical intervention is similar to the study made by Erdogan et al [9] where 26% of the patients who were operated on immediately had complications and none of the patients who were treated conservatively. Another study, by Roach JP et al [11] showed complication rate requiring readmission to the hospital of 10% in the operated patients which was significantly higher than the conservatively treated children.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore they doubt if there is a role for interval appendectomy as part of an institutional treatment protocol. In contrast, Erdogan et al [9] promoted interval appendectomy after conservative treatment; they evaluated that the risk of recurrence to be 76.2%. Samuel et al [7] have also concluded that interval appendectomy is recommended after nonsurgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Wound infection, as a minor problem, can be seen more frequently in patients with immediate appendectomy. [19,20] The rate of wound infection was found as 27.7% in our series, which is relatively high. Arshad et al [21] reported wound sepsis in 19.31% of their patients after immediate appendectomy due to appendiceal mass.…”
Section: Discussionmentioning
confidence: 46%